KETIKA MISI BERSINGGUNGAN DENGAN IDENTITAS AGAMA LAIN: TINJAUAN ETIS BERMISI LEWAT TIKTOK - Marva Pai; Linda Ratag (PT. Giat Konseling Nusantara, 2026)
This research is a literature study that explores the role of social media in the context of the church's mission, especially in efforts to reach and influence apologists in the digital age. The digital age has changed the way people interact, learn, and seek information, and churches have had to adapt to be relevant in fulfilling their mission. This study uses a qualitative approach with content analysis of Christian mission content on TikTok with several digital mission actors. The aim is to understand how messages of faith are constructed, conveyed and received in the context of a multireligious society in the digital space. The results show that the practice of mission on TikTok presents two sides: great potential in reaching the digital generation and affirming faith, but also ethical risks when missions are carried out without considering the sensitivity of other religions. From an ethical review, this study confirms the importance of carrying out the mission in a relevant way and contextual awareness. Reflective, communicative, and exclusive missions not only demonstrate faithfulness to Christ, but also present a peaceful testimony in the midst of a diversity of religious identities. By analyzing the existing literature, this study tries to answer some key questions that pose ethical dilemmas: how to stay true to the call to mission without hurting or offending other religious identities? God's mission must be accomplished.